Using Team Topologies in Model-Driven Strategic Alignment - Noel, Rene; Panach Navarrete, Jose Ignacio; Pastor, Oscar (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2023: Anais do XXVI Congresso Ibero-Americano em Engenharia de Software, 2023)
Model-driven techniques for designing strategically aligned information systems usually map the goals of multiple and competing actors to business process models through automatic model-to-model transformations and analysis. In previous work, we designed Stra2Bis, a method for designing strategically aligned business processes based on a different approach: mapping the business strategy and organisation structure into the business process model. Stra2Bis and goal-based techniques share an issue: only some organisational level elements actors directly affect the business domain and, thus, the business processes. In this article, we propose to extend Stra2Bis by adding concepts from Team Topologies, an approach for organising business and technology teams. Team Topologies help distinguish the business-relevant organisation units from other supporting units; we exploit these concepts to constrain the model-to-model mappings, avoiding unnecessary analysis and modelling outside the business domain. We formalise the approach by specifying the method's metamodel extension and redefining the model-to-model transformation guidelines. We also discuss how existing goal-based alignment frameworks can exploit this approach.